NEW MEGALOCYTIVIRUS INFECTED TO THE CULTURED FRESH WATER GIANT GOURAMI, Osphronemus gouramy Lac. IN INDONESIA - Isti Koesharyani; Lila Gardenia (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2013)
Giant gourami (Osphronemus gouramy Lac.) is one of freshwater fish having high economic value and very popular in Indonesian food restaurant. This fish have been cultured throughout Indonesia. Since two years ago, cultured fish in ponds infected by unknown pathogenic agent and may cause diseased fish and mass mortality. Mass mortality of pond cultured giant gourami occurred in West Java, Central Java, and Bali-Indonesia. The symptoms of diseased fish are the body color becomes darker, resting on the water surface, and internal organs of fish characterized by enlargement of spleen. In the present study diseased fish samples were diagnose by Polymerase Chain Reaction (PCR) techniques using specific primers of red sea bream iridovirus (RSIV) and histopathologically analysis to determine the causative agent of mortality. Based on PCR analysis, show that all fish sampled were positive infected by megalocytivirus and infected fish mostly died. This is a new and first time reported virus infection in cultured giant gourami in Indonesia and it is proposed to be named as giant gourami iridovirus (GGIV).